(3CSQGQ GdJfRjd hCfhGQ GdJChjds - (3GdTjN CQSdGfs
(3ChdgG (B:s
(3jHOC HGdHGH GdChd ai JbQjQ cjajI OdGdI GdSehGJ Ydi EKHGJ s
(3BNQgG (B:s
(3jfJgi HGdeQJHI GdNGeSI chfg eNdhbkG ef Wjf dGRH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B83s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ , HgG NQe s
(3GdfSNI HgG JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs